1996
DOI: 10.1088/0957-0233/7/10/021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of humidity on hot-wire measurements

Abstract: When applying hot-wire anemometry to velocity measurements in air, it is standard practice to neglect the effect of humidity. In this paper the influence of the thermodynamic and transport properties of humid air on hot-wire measurements is examined on the basis of the correlations for Nusselt number proposed previously by other researchers. Experimental results at controlled levels of relative humidity between 30% and 90% at 30 • C, 50 • C and 70 • C are reproduced satisfactorily by the theoretical approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…In our case, i.e. for stratospheric conditions, the density varies between 1.2 kg/m 3 and ∼ 1.0×10 −2 kg/m 3 , the (relative) wind velocities are up to 2 m/s and the temperature decreases to ∼200 K. The water vapour mixing ratio in the stratosphere amounts to ∼5 ppm and therefore the influence on our measurements is negligible (Durst et al, 1996).…”
Section: Constant Temperature Anemometrymentioning
confidence: 70%
See 2 more Smart Citations
“…In our case, i.e. for stratospheric conditions, the density varies between 1.2 kg/m 3 and ∼ 1.0×10 −2 kg/m 3 , the (relative) wind velocities are up to 2 m/s and the temperature decreases to ∼200 K. The water vapour mixing ratio in the stratosphere amounts to ∼5 ppm and therefore the influence on our measurements is negligible (Durst et al, 1996).…”
Section: Constant Temperature Anemometrymentioning
confidence: 70%
“…The crucial point is that the calibration coefficients are only valid if the ambient conditions do not differ from those during the calibration. This concerns not only the wind conditions, but also the density, temperature and humidity (Cimbala and Park, 1990;Cardell, 1993;Durst et al, 1996;Hugo et al, 1999). Thus the calibration should be performed under ambient conditions similar to the conditions during the measurements.…”
Section: Constant Temperature Anemometrymentioning
confidence: 99%
See 1 more Smart Citation
“…For the anemometer, sensitivity increased slightly as humidity increased and then decreased by 28% at high humidity levels. Durst et al derived theoretical calculations for the thermal conductivity of air and found that the highest conductivity occurred at medium humidity levels (30 to 40 %RH depending on air temperature) [11]. We think that the initial increase in sensitivity is due to the change in thermal conductivity of the moist air.…”
Section: Humidity Coefficient Of Sensitivitymentioning
confidence: 87%
“…Although most commercially available thermal anemometer sensors automatically compensate for changes in air temperature, there is no correction for changes in barometric pressure or air humidity. The error in air velocity due to changes in barometric pressure can be upward of 12% (Johnston and Fleeter, 1997) and upward of 13% due to changes in air humidity (Durst et al, 1996).…”
Section: Airflow Rate Measurement Techniquesmentioning
confidence: 99%